PELAKSANAAN FUNGSI LEMBAGA ADAT KENEGERIAN LIPAT KAIN DI KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR - Yolanda Nur Amalia; Rury Febrina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Law Number 6 of 2014 concerning Villages places the Village Customary Institution as an institution that carries out traditional functions and is part of the original structure of the village that grows and develops on the initiative of the village community whose task is to assist the Village Government and as partners in empowering, preserving, and developing customs as a form of recognition of the customs of the village community.The purpose of this research is to first find out the Implementation of the Functions of Kenegerian Fold Fabric Indigenous Institutions in Kampar Kiri District of Kampar Regency. Second To find out what are the factors that inhibit The Implementation of the Functions of Kenegerian Fold Fabric Indigenous Institutions in Kampar Kiri District of Kampar Regency.The theoretical concept used by the author is Law No. 6 of 2014 concerning Villages namely Empowerment, Preservation and development. In this study the authors used the methodqualitative approach with descriptive studies.The results of this study indicate three roles of traditional institutions namely empowerment, preservation and development of thatCustomary institutions still play their role in empowering customs and community involvement in supporting customs activities in Kenegerian Lipat Kain is still held firmly from the past until now. While the role of traditional institutions in preserving customs in Kenegerian Fold Kain by making various effortsso that the values of customs and traditions are not lost, among others by conducting training, counseling and promoting the community. Then there are severalthe development of traditional activities in the Cloth Folding Kenegerian, but there are also some customary activities that have begun to change and disappear with the times. Inhibiting factors includeThe lack of good relations between adat instruments in Kenegerian Lipat Kain, lack of budget, lack of community interest and weak coordination between adat institutions, village government and communities.Keywords: Implementation, Function, Customary Institutions, Customary Customs.